PERILAKU TEMAN SEBAYA MENINGKATKAN KEJADIAN BULLYING PADA REMAJA - Herlyssa Herlyssa; Nina Primasari; Qhistya Rizka Alhaq (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Bullying still occurs in adolescents. Indonesia is the second country for the occurrence of bullying cases from the 40 countries surveyed. This study aims to determine the description of bullying in adolescents in DKI Jakarta. The research design was a analitic study with a cross sectional approach. The population in this study were adolescents in DKI Jakarta, the sampling technique used was accidental sampling. The results showed that adolescents who experienced bullying in DKI Jakarta in 2020 amounted to 35%. There is a significant relationship between peer behavior and the incidence of bullying in adolescents. The most dominant variable is peer behavior with an OR value of 5.625 (95% CI = 1.543-20.511), which means that adolescents who get negative behavior from peers have a chance of 5.625 times to experience bullying behavior. So that the midwife as a woman's friend is expected to be a good friend, someone who is warm, close, and fun to adolescents, and also creates good relationships with adolescent.